2011
DOI: 10.1007/s11999-011-1791-4
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Localize The Radial Nerve Using the ‘Apex Of Triceps Aponeurosis’ as a Landmark

Abstract: Background The relationship of the radial nerve is described with various osseous landmarks, but such relationships may be disturbed in the setting of humerus shaft fractures. Alternative landmarks would be helpful to more consistently and reliably allow the surgeon to locate the radial nerve during the posterior approach to the arm. Questions/purposes We investigated the relationship of the radial nerve with the apex of triceps aponeurosis, and describe a technique to locate the nerve. Materials and MethodsWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…A study that was performed on cadavers and sixty patients measured the distance of the radial nerve from this apex. Those results indicate that the distance of the radial nerve was consistently about 2.5 cm from the apex of the triceps aponeurosis 54 .…”
Section: Treatment For Radial Nerve Palsymentioning
confidence: 63%
“…A study that was performed on cadavers and sixty patients measured the distance of the radial nerve from this apex. Those results indicate that the distance of the radial nerve was consistently about 2.5 cm from the apex of the triceps aponeurosis 54 .…”
Section: Treatment For Radial Nerve Palsymentioning
confidence: 63%
“…In 2011, Arora et al examined the position of the nerve in relation to the apex of the aponeurosis in both the cadaveric and the operative setting. 35 It was noted that the nerve could reliably be located 25 mm proximal to the apex of the aponeurosis. This correlates with and supports our finding of the nerve positioned 21.8 mm from this point (referred to as the medial apex of the aponeurosis).…”
Section: Discussionmentioning
confidence: 99%
“…The radial nerve arises from the ventral branches of the nervi spinalis C7–Th1. It then creates the posterior cord of the brachial plexus [ 8 ]. Together with the accompanying vessels, it then proceeds from the medial side to the side of the posterior surface of the humerus in the groove of the radial nerve, and on the border of the middle and distal 1/3 of the humeral shaft turns to the side-arm front surface [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ]. Other studies have indicated a higher course for the radial nerve, from the proximal humerus (53% of the humeral length) at 12.0±2.3 cm (range, 7.4–16.6 cm) and from the olecranon fossa (36% of the humeral length) at 16.0±0.4 cm (range, 9.0–20.5 cm) [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation